2000
DOI: 10.1046/j.1365-2958.2000.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigens are targeted by diverse strains of typable and non‐typable Haemophilus influenzae

Abstract: SummaryHaemophilus influenzae (Hi), a commensal of the human respiratory mucosa, is an important cause of localized and systemic infections. We show that distinct strains belonging to typable (THi) and nontypable (NTHi) H. influenzae target human carcinoembryonic antigens (the membrane associated CEA family of cell adhesion molecules, are now termed CEACAMs). All strains of H. influenzae biogroup aegyptius (Hi-aeg) and more than 70% of THi and NTHi strains tested specifically recognize CEACAMIFc soluble constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 43 publications
3
106
0
Order By: Relevance
“…It is likely that this complex set of effects arises as a result of the numerous homophilic and heterophilic interactions that CEACAM1 can have with itself and other members of the CEACAM superfamily. The N-terminal Ig variable (Ig V ) domain of CEACAM1 has been suggested to be the basis of cis and trans homo-dimer formation (20), as well as interactions with other molecules (21)(22)(23)(24). There are crystal structures of the Ig V domain expressed in Escherichia coli, which have led to the suggestion of two distinct dimerization interfaces (24,25).…”
mentioning
confidence: 99%
“…It is likely that this complex set of effects arises as a result of the numerous homophilic and heterophilic interactions that CEACAM1 can have with itself and other members of the CEACAM superfamily. The N-terminal Ig variable (Ig V ) domain of CEACAM1 has been suggested to be the basis of cis and trans homo-dimer formation (20), as well as interactions with other molecules (21)(22)(23)(24). There are crystal structures of the Ig V domain expressed in Escherichia coli, which have led to the suggestion of two distinct dimerization interfaces (24,25).…”
mentioning
confidence: 99%
“…Moreover, when combined with their phenomenal ability to alter its surface structures (41), their subversion of CEACAM1 coinhibitory function suggests that the bacteria persist by stealth, both escaping and actively suppressing the adaptive immune response. Considering that other human restricted-pathogens including Neisseria meningitidis (16), Haemophilus influenzae (57), and Moraxella catarrhalis (58), each bind CEACAM1, it is enticing to speculate that these pathogens also share this effective evolutionary strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, selective FimH-binding mannosides have been indicated in preventing UTIs in a preclinical murine model [106]. In vitro studies have found that anti-CEACAM antibodies block the adhesion of M. catarrhalis, N. meningitidis and NTHi to airway epithelial cells [39,71,107]. Also, NTHi adherence to A549 alveolar epithelial cells in vitro was shown to be inhibited in a dose-dependent manner with increasing concentrations of anti-ICAM-1 monoclonal antibodies [52].…”
Section: Inhibiting Specific Bacterial Adhesin-host Receptor Interactmentioning
confidence: 99%